Systematic review of how Play Streets impact opportunities for active play, physical activity, neighborhoods, and communities - M. Renée Umstattd Meyer; Christina N. Bridges; Thomas L. Schmid; Amelie A. Hecht; Keshia M. Pollack Porter (BMC, 2019)
Abstract Background Active play and physical activity are important for preventing childhood obesity, building healthy bones and muscles, reducing anxiety and stress, and increasing self-esteem. Unfortunately, safe and accessible play places are often lacking in under-resourced communities. Play Streets (temporary closure of streets) are an understudied intervention that provide safe places for children, adolescents, and their families to actively play. This systematic review examines how Play Streets impact opportunities for children and adolescents to engage in safe active play and physical activity, and for communities and neighborhoods. Methods for evaluating Play Streets were also examined. Methods A systematic literature review was conducted in Academic Search Complete, CINHAL, PsycINFO, PubMED, Web of Science, and Google Scholar. Peer-reviewed intervention studies published worldwide were included if they were published in English, through December 2017 and documented free-to-access Play Streets or other temporary spaces that incorporated a designated area for children and/or adolescents to engage in active play. Systematic data extraction documented sample, implementation, and measurement characteristics and outcomes. Results Of 180 reviewed abstracts, 6 studies met inclusion criteria. Studies were conducted in five different countries (n = 2 in U.S.), using mostly cross-sectional study designs (n = 4). Physical activity outcomes were measured in half of the studies; one used observational and self-report measures, and two used device-based and self-report measures. In general, Play Streets provided safe places for child play, increased sense of community, and when measured, data suggest increased physical activity overall and during Play Streets. Conclusions Play Streets can create safe places for children to actively play, with promise of increasing physical activity and strengthening community. Given the popularity of Play Streets and the potential impact for active play, physical activity, and community level benefits, more rigorous evaluations and systematic reporting of Play Streets' evaluations are needed.